Efficacy of behavior change communication using mobile calls on glycemic control among Type 2 diabetic patients in an urban area of Pondicherry, South India: A randomized controlled trial - B Jayasree; P Stalin (Wolters Kluwer Medknow Publications, 2019)
CONTEXT: Lifestyle modifications play a major role in controlling blood glucose levels among diabetes mellitus for the prevention of its complications. Mobile phones can be used as an efficient tool for improving the healthy lifestyle through health education. AIMS: The aim of the study is to measure the efficacy of behavior change communication using mobile calls in controlling blood sugar levels, increasing medication adherence, healthy diet, and physical activity among diabetic patients. SETTINGS AND DESIGN: A randomized controlled trial was conducted in an urban area of Pondicherry between 50 (25 per arm) type 2 diabetes patients. SUBJECTS AND METHODS: All participants were interviewed using a structured questionnaire. Fasting blood glucose (FBG) was measured. Single-time health education was given to both groups. The intervention group received a mobile phone calls reminders thrice weekly for 2 months. Changes in FBG, diet, physical activities, and adherence to medications were assessed after 2 months. STATISTICAL ANALYSIS USED: Means and proportions were calculated. Chi-square test and paired t-test were used to calculate the P value. RESULTS: FBG increased significantly in the control group by 25.6 mg/dl (P = 0.03), whereas it was only 6.5 mg/dl in the intervention group (P = 0.56). Adherence to medications was increased significantly in both interventions (+21%) and control (+19%) groups. Number of fruits intake days per week (+1, P = 0.01) and fruits serving per day (+0.5, P = 0.00) have increased significantly in the intervention group. Recreational physical activity was increased in the intervention group but not statistically significant. CONCLUSION: Our study findings suggest that mobile phone calls might help to improve glycemic control. It also suggests that it could improve the adherence to medications and intake of fruits. In the future, studies with large sample size and longer intervention need to be conducted.